Clinical efficacy of spleen-preserving distal pancreatectomy with or without splenic vessel preservation: A Meta-analysis. Issue 48 (December 2017) - Sun, Ningning; Lu, Guangjun; Zhang, Likun; Wang, Xiaoling; Gao, Chunmin; Bi, Jieliang; Wang, Xiaoyi
Abstract: Objective: The meta-analysis was performed to investigate the clinical efficacy of spleen-preserving distal pancreatectomy with splenic vessel preservation (SPDP-SVP) and spleen-preserving distal pancreatectomy with splenic vessel resection (SPDP-SVR). Methods: Potential articles were searched on the databases of Pubmed, Embase, and Chinese National Knowledge Infrastructure (CNKI) from January 1988 until March 2017. Weight mean difference (WMD) with 95% confidence interval (CI) was applied to compare the efficacy of SPDP-SVP and SPDP-SVR. Odds ratio (OR) with 95% CI was calculated to figure out the risks for complications. P < .05 or I 2 >50% indicated significant heterogeneity. The random-effects model is used to pool data if significant heterogeneity exists; otherwise, the fixed-effects model is used. Publication bias was evaluated by Begg's funnel plot. Results: Thirteen eligible articles were obtained in the meta-analysis. SPDP-SVP seemed to relate with reduced operative time and blood loss, prolonged hospital stay, and less complications; however, the effects were not statistically significant. Meanwhile, we found that SPDP-SVP was closely related with the reduced rate of splenic infarction and gastric varices (OR = 0.16, 95% CI = 0.09–0.29; OR = 0.08, 95% CI = 0.02–0.35). No publication bias was observed in the analysis ( P = .636). Conclusions: SPDP-SVP seems to show superiority than SPDP-SVR in reducing the rate of splenic infarction and gastric varices.